PARP1 blockade is synthetically lethal in XRCC1 deficient sporadic epithelial ovarian cancers. (28th January 2020) - Ali, Reem; Alabdullah, Muslim; Alblihy, Adel; Miligy, Islam; Mesquita, Katia A.; Chan, Stephen YT.; Moseley, Paul; Rakha, Emad A.; Madhusudan, Srinivasan
Abstract: PARP1 inhibitor (Niraparib, Olaparib, Rucaparib) maintenance therapy improves progression-free survival in platinum sensitive sporadic epithelial ovarian cancers. However, biomarkers of response to PARPi therapy is yet to be clearly defined. XRCC1, a scaffolding protein, interacts with PARP1 during BER and SSBR. In a large clinical cohort of 525 sporadic ovarian cancers, high XRCC1 or high PARP1 protein levels was not only associated with aggressive phenotypes but was also significantly linked with poor progression-free survival (p = 0.048 & p = 0.001 respectively) and poor ovarian cancer-specific survival (p = 0.020 & p = 0.008 respectively). Pre-clinically, Olaparib and Talazoparib therapy were selectively toxic in XRCC1 deficient or knock-out platinum sensitive ovarian cancer cells in 2D and 3D models. Increased sensitivity was associated with DNA double-strand break accumulation, cell cycle arrest and apoptotic cell accumulation. We conclude that XRCC1 deficiency predicts sensitivity to PARP inhibitor therapy. PARP1 targeting is a promising new approach in XRCC1 deficient ovarian cancers. Highlights: XRCC1 is a key protein with roles in BER, SSBR and alt-NHEJ DNA repair. XRCC1 deficiency is a predictor of platinum sensitivity in clinical ovarian cancer. Olaparib or Talazoparib therapy is synthetically lethal in XRCC1 deficient cancers. PARP1 targeting is a novel approach in XRCC1 deficient ovarian cancers.